FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE : SYSTEMATIC LITERATURE REVIEW - Nur Malikha Ulfah; Ihsan, Muhammad; Rhofitania, Rhofitania; Wahono, Puji; Pahala, Indra (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Taxes are an important component that is the main source of state income. One of the tax objects is corporate and corporate taxpayers who are obliged to pay to the government, but the taxpayer does not volunteer to pay taxes and tries to pay as little tax as possible so as not to reduce the income or net profit of a company. This is what drives companies to do tax avoidance by easing the tax burden. The purpose of this study is to find out the factors that affect tax avoidance and identify how much research results on tax avoidance in Sinta provide understanding and its relevance to existing phenomena or problems in Indonesia. The method used in this study was the Systematic Literature Review (SLR), where researchers reviewed 8 journals related to the Sinta-indexed economy, then 16 articles were obtained that discussed tax avoidance. The results of this research show that there are many factors that affect tax avoidance in Indonesia, especially with the implementation of good corporate governance and supported by using control variables such as leverage, company size, the board of commissioners can reduce avoidance practises. Tax avoidance by companies has the benefit of reducing the burden, but has an impact and risk with a decrease in the company's image. Key Words: Tax Avoidance, Good Corporate Governance, SLR